Enhancing Student Performance Prediction Using Deep Belief Networks with Ant Lion Optimization - M. Kannan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Educational institutions need to predict student performance accurately in order to provide timely interventions. However, researchers often struggle to capture the complexity of student-related data, which leads to suboptimal predictions. This research proposes that we leverage deep belief networks (DBNs) and ant lion optimisation (ALO) to enhance student performance prediction. The methodology includes collecting data, preprocessing it, selecting features using ALO, training DBNs for feature learning and classification, evaluating the model, and conducting comparative analysis. The study investigates the effectiveness of DBNs in predicting student performance, explores ALO for feature selection, develops a robust methodology integrating DBNs and ALO, and evaluates the approach on real-world datasets. The results demonstrate that the proposed approach improves prediction accuracy and f-measure compared to the existing methods.